The two faces of Janus? Anxiety and enjoyment in the foreign language classroom - Dewaele, Jean-Marc; MacIntyre, Peter D. (Studies in Second Language Learning and Teaching, 2014)
The present study investigates Foreign Language Enjoyment (FLE) and Foreign Language Classroom Anxiety (FLCA) in the classroom. Participants were 1746 current FL learners from around the world. We used a measure of FLE, based on Likert scale ratings of 21 items (Dewaele & MacIntyre, 2014), and a measure of FLCA based on 8 items extracted from the FLCAS (Horwitz, Horwitz, & Cope, 1986). Statistical analyses revealed that levels of FLE were significantly higher than those of FLCA. FLE and FLCA were linked to a number of independent variables: participants’ perception of their relative level of proficiency within the FL classroom, number of languages known, education level, number of FLs under study, age group and general level of the FL (ranging from lower-intermediate to advanced). Female participants reported both more FLE and more FLCA. Cultural background of participants also had a significant effect on their scores. Participants’ views on episodes of enjoyment in the FL class revealed the importance of teachers’ professional and emotional skills and of a supportive peer group. Many participants mentioned the moment at which they realised that their long effort in mastering an aspect of the FL paid off.